Area deprivation and respiratory morbidities in children with bronchopulmonary dysplasia. Issue 9 (21st May 2022) - Banwell, Emma; Collaco, Joseph M.; Oates, Gabriela R.; Rice, Jessica L.; Juarez, Lucia D.; Young, Lisa R.; McGrath‐Morrow, Sharon A.
Abstract: Introduction: Infants and children diagnosed with bronchopulmonary dysplasia (BPD) have a higher likelihood of recurrent hospitalizations and asthma‐like symptoms. Socio‐environmental factors that influence the frequency and severity of pulmonary symptoms in these children during the preschool age are poorly understood. In this study, we used the Area Deprivation Index (ADI) to evaluate the relationship between the socio‐environmental exposures in children with BPD and respiratory outcomes during the first few years of life. Methods: A registry of subjects recruited from outpatient BPD clinics at Johns Hopkins University ( n = 909) and the Children's Hospital of Philadelphia ( n = 125) between January 2008 and October 2021 was used. Subjects were separated into tertiles by ADI scores aggregated to ZIP codes. Caregiver questionnaires were used to assess the frequency of respiratory morbidities and acute care usage for respiratory symptoms. Results: The mean gestational age of subjects was 26.8 ± 2.6 weeks with a mean birthweight of 909 ± 404 g. The highest tertile (most deprived) of ADI was significantly associated with emergency department visits (aOR 1.72; p = 0.009), hospital readmissions (aOR 1.66; p = 0.030), and activity limitations (aOR 1.55; p = 0.048) compared to the lowest tertile. No association was seen with steroid, antibiotic or rescue medication use, trouble breathing, or nighttime symptoms. Conclusion: In this study, children with BPD who lived in areas of higher deprivation were more likely to be rehospitalized and have ED visits for respiratory reasons. Identifying socio‐environmental factors that contribute to adverse pulmonary outcomes in children with BPD may provide opportunities for earlier interventions to improve long‐term pulmonary outcomes.